The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-2415-13-41
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic techniques for inflammatory eye disease: past, present and future: a review

Abstract: Investigations used to aid diagnosis and prognosticate outcomes in ocular inflammatory disorders are based on techniques that have evolved over the last two centuries have dramatically evolved with the advances in molecular biological and imaging technology. Our improved understanding of basic biological processes of infective drives of innate immunity bridging the engagement of adaptive immunity have formed techniques to tailor and develop assays, and deliver targeted treatment options. Diagnostic techniques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 110 publications
0
5
0
Order By: Relevance
“…Despite the rarity, uveal EMZL should be included in the differential diagnosis of uveal inflammation or tumors, particularly in patients with persistent signs and symptoms. Non-resolving or recurrent masquerade syndromes not responding to standard treatment should lead to prompt biopsy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rarity, uveal EMZL should be included in the differential diagnosis of uveal inflammation or tumors, particularly in patients with persistent signs and symptoms. Non-resolving or recurrent masquerade syndromes not responding to standard treatment should lead to prompt biopsy [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has observed that mantoux test can be used for the diagnosis of ocular TB, which remains to be least invasive and cost effective procedure. The drawback being that the tuberculin skin test cannot differentiate between infections of Mycobacterium TB from that of atypical Mycobacteria [17]. An epidemiological report published recently from Korea has indicated that with a reaction of >10 mm diameter taken as a cut off, there has been a decrease in the positivity against tuberculin skin test from 2005 (28%) to 2009 (15%), which was associated to BCG vaccination [18].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced imaging tools (such as MRI or ultra sono graphy) enable direct visualization and accurate measure ment of joint specific inflammation, at the same time, 9 tools that determine the severity of ocular disease (such as levels of cytokines in tears, impres sion cyto logy, automated grading of conjunctival hyperae mia and in vivo imag ing of immune cells and lymphatics) have advanced the study of ocular surface immun ology. 10 Knowledge of shared and organspecific processes should shape em erging and future therapeutic approaches to dry eye.…”
Section: Introductionmentioning
confidence: 99%